2014
DOI: 10.1053/j.seminoncol.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment in Head and Neck Squamous Cell Carcinoma

Abstract: The tumor microenvironment (TME) of head and neck squamous cell carcinoma (HNSCC) is comprised of cancer-associated fibroblasts (CAFs), immune cells, and other supporting cells. Genetic changes in the carcinoma cells, such as alterations to TP53, NOTCH1, and specific gene expression profiles, contribute to derangements in cancer and microenvironment cells such as increased ROS, overproduction of cytokines, and epithelial to mesenchymal transition (EMT). CAFs are among the most critical elements of the TME cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
205
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(213 citation statements)
references
References 178 publications
5
205
0
3
Order By: Relevance
“…A study utilized next-generation sequencing and identified EGFR as one of the most commonly mutated cancer-related gene in OSCC [31] and it is also considered a major player in oral carcinogenesis [32] as it was found to harbour genetic alterations as a result of repeated exposure to risk factors [19]. According to Gupta et al, EGFR overexpression lead to lower overall survival, overall response and quality of life in patients with locally advanced OSCC who had been treated with chemoradiation [33].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…A study utilized next-generation sequencing and identified EGFR as one of the most commonly mutated cancer-related gene in OSCC [31] and it is also considered a major player in oral carcinogenesis [32] as it was found to harbour genetic alterations as a result of repeated exposure to risk factors [19]. According to Gupta et al, EGFR overexpression lead to lower overall survival, overall response and quality of life in patients with locally advanced OSCC who had been treated with chemoradiation [33].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…There is evidence that all components of the tumor stroma can critically influence carcinogenesis and the malignant phenotype in multiple stages of tumor development [5,6]. Among these components, CAFs, fibroblast-like cells that acquire the ability to express isoform α of the smooth muscle actin (α-SMA) and synthesize an extensive repertoire of cytokines, growth factors, chemokines, hormones, neurotransmitters, inflammatory mediators, adhesion proteins, and most abundantly extracellular matrix proteins, have been highlighted as the major player in tumor-stroma cross talk [7].…”
Section: Introductionmentioning
confidence: 99%
“…Though it is considered that inflammation creates a beneficial effect in the removal of pathological structures and in the destruction of cancer cells, inflammatory response that is unorganized and managed by the cancer cells creates an opportunity for the development of the tumor and for the cancer cells to evade the devastating effects of the immune system. Research conducted in head and neck cancers have clearly revealed that local, regional, and systemic inflammatory responses are dysfunctional (16,17).…”
Section: The Effect Of Inflammatory Cells Around the Microenvironmentmentioning
confidence: 99%
“…Undergoing myofibroblastic changes, these cells have a phenotype characterized by dense ultrastructural α-smooth muscle actin deposition. In addition, integrin α6 overexpression, which is important in cell adhesion and surface signaling, is also determined (17).…”
Section: The Effect Of Inflammatory Cells Around the Microenvironmentmentioning
confidence: 99%